An observational study on the relationship between dynamic balance and gluteus medius endurance in flat foot among individuals aged 18–25 years - Fathimath Shabeeba T P; Riyas Basheer K B; Subhashchandra Rai; Royline Fathima Pinto; Reshma Kolar (Journal of Orthopaedic Reports)
Background: Flat feet, a condition where the arches of the foot collapse, can impair balance and gait. The gluteus medius muscle, a key stabilizer of the hip, plays an important role in maintaining lower extremity stability, and its endurance may influence dynamic balance. However, the relationship between gluteus medius endurance and dynamic balance in individuals with flat feet remains unclear. Objective: To explore the relationship between dynamic balance and gluteus medius endurance in individuals aged 18–25 with flat feet. Methods: This observational study was conducted over an eight-month period from March to November 2023at a college in Mangalore, Karnataka. The study included 50 participants aged 18–25 diagnosed with flat feet based on the Navicular Drop Test (NDT). Dynamic balance was assessed using the Y Balance Test (YBT), and gluteus medius endurance was measured through the Gluteus Medius Abduction Endurance Test. Statistical analysis was performed using SPSS version 21.0, with Spearman correlation to examine the relationship between the variables. Results: The results revealed a weak positive correlation between gluteus medius endurance and dynamic balance on the left side (r = 0.243, p = 0.132), though not statistically significant. No significant correlation was found on the right side (r = −0.020, p = 0.905). The study also found that other factors, such as age, weight, and BMI, did not significantly affect the relationship between gluteus medius endurance and dynamic balance. Conclusion: The study suggests that gluteus medius endurance has a limited influence on dynamic balance in individuals with flat feet. A weak correlation was found on the left side, but no significant relationship was observed on the right side. Further research should incorporate other factors like core stability and tibialis posterior strength to better understand the dynamics influencing balance in flat-footed individuals.